Ten-step asymmetric total syntheses of potent antibiotics anthracimycin and anthracimycin B. Issue 43 (25th October 2022) - Tian, Peilin; Ye, Wenkang; Zhang, Xiayan; Tong, Yi; Qian, Pei-Yuan; Tong, Rongbiao
Abstract : A convergent protecting-group free 10-step total synthesis of anthracimycin and anthracimycin B (first) was achieved, featuring cascade vinylogous Mukaiyama Aldol and intramolelucular Diels–Alder reaction and Z-selective ring-closing metathesis. Abstract : The increase in antibiotic resistance calls for the development of novel antibiotics with new molecular structures and new modes of action. However, in the past few decades only a few novel antibiotics have been discovered and progressed into clinically used drugs. The discovery of a potent anthracimycin antibiotic represents a major advance in the field of antibiotics. Anthracimycin is a structurally novel macrolide natural product with an excellent biological activity profile: (i) potent in vitro antibacterial activity (MIC 0.03–1.0 μg mL −1 ) against many methicillin-resistant Staphylococcus aureus (MRSA) strains, Bacillus anthracis (anthrax), and Mycobacterium tuberculosis ; (ii) low toxicity to human cells (IC50 > 30 μM); (iii) a novel mechanism of action (inhibiting DNA/RNA synthesis). While the first total synthesis of anthracimycin was elegantly accomplished by Brimble et al. with 20 steps, we report a 10-step asymmetric total synthesis of anthracimycin and anthracimycin B (first total synthesis). Our convergent strategy features (i) one-pot sequential Mukaiyama vinylogous aldol/intramolecular Diels–Alder reaction to construct trans -decalin with high yield and excellent endo / exo selectivity and (ii) Z -selective ring-closing metathesis to forge the 14-membered ring. In vitro antibacterial evaluation suggested that our synthetic samples exhibited similar antibacterial potency to the naturally occurring anthracimycins against Gram-positive strains. Our short and reliable synthetic route provides a supply of anthracimycins for further in-depth studies and allows medicinal chemists to prepare a library of analogues for establishing structure–activity relationships.